ЎЗБЕКИСТОН ШАРОИТИДА ЭЧКИЛАР (CAPRA HIRCUS L.) ГЕЛЬМИНТЛАРИНИ ЎРГАНИЛИШ ҲОЛАТИ - Дадаев, С.; Палўаниязова, Д.А. (SCIENCE and SOCIETY, 2022)
This article provides information about the fauna of helminths found in goats in different biocenoses of Uzbekistan.